Demystifying the RAD fad. Issue 24 (December 2014) - Puritz, Jonathan B.; Matz, Mikhail V.; Toonen, Robert J.; Weber, Jesse N.; Bolnick, Daniel I.; Bird, Christopher E.
<x xml:space="preserve">Abstract</x> We are writing in response to the population and phylogenomics meeting review by Andrews & Luikart (2014) entitled 'Recent novel approaches for population genomics data analysis'. Restriction‐site‐associated DNA (RAD) sequencing has become a powerful and useful approach in molecular ecology, with several different published methods now available to molecular ecologists, none of which can be considered the best option in all situations. A&L report that the original RAD protocol of Miller et al. (2007) and Baird et al. (2008) is superior to all other RAD variants because putative PCR duplicates can be identified (see Baxter et al. 2011), thereby reducing the impact of PCR artefacts on allele frequency estimates (Andrews & Luikart 2014). In response, we (i) challenge the assertion that the original RAD protocol minimizes the impact of PCR artefacts relative to that of other RAD protocols, (ii) present additional biases in RADseq that are at least as important as PCR artefacts in selecting a RAD protocol and (iii) highlight the strengths and weaknesses of four different approaches to RADseq which are a representative sample of all RAD variants: the original RAD protocol (mbRAD, Miller et al. 2007; Baird et al. 2008), double digest RAD (ddRAD, Peterson et al. 2012), ezRAD (Toonen et al. 2013) and 2bRAD (Wang et al. 2012). With an understanding of the strengths and weaknesses of different RAD protocols, researchers can make a more informed decision when selecting a RAD protocol.